(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explains the four primary sentence structures in English simple, compound, complex, and compound-complex—by detailing their unique characteristics, functions, and examples. The text starts with an overview, then breaks down each sentence type, highlighting how each structure contributes to clarity, rhythm, and coherence in writing. The simple sentence provides directness, the compound sentence links ideas, the complex sentence introduces depth, and the compound-complex sentence combines complexity with connection. A summary table reinforces these differences, while the concluding sections emphasize the importance of mastering sentence structures to enhance communication skills. This clear explanation equips readers with a foundational understanding of sentence structure, helping them diversify and refine their language use.